Application of dynamic vibration absorbers in designing a vibration isolation track at low-frequency domain. (May 2017) - Zhu, Shengyang; Yang, Jizhong; Cai, Chengbiao; Pan, Zili; Zhai, Wanming
This paper aims to develop a low-frequency vibration isolation track based on passive vibration isolation theory and vehicle–track interaction analysis. First, a preliminary low-frequency vibration isolation track is proposed by attaching multiple dynamic vibration absorbers to a discontinuous floating slab track, and the optimal design parameters of the multidynamic vibration absorber are determined by searching the minimum values of two assessment functions. Further, a three-dimensional coupled dynamic model of a metro vehicle and the low-frequency vibration isolation track is established by using Ansys Parametric Design Language, where the equations of motion of the vehicle subsystem and the wheel–rail contact calculations are incorporated in the software Ansys using the Ansys Parametric Design Language, and the low-frequency vibration isolation track subsystem is directly created by using common elements in Ansys. The vibration isolation performance of the preliminary low-frequency vibration isolation track with multidynamic vibration absorber is investigated under harmonic load and vehicle dynamic load, respectively. Results show that the slab acceleration and supporting force are significantly reduced at low frequencies of 10–20 Hz compared with those of the traditional floating slab tracks. Finally, an improved low-frequency vibration isolation track is developed for actual manufacturing and practical application, and simulations show that the improved low-frequency vibration isolation track exhibits a more robust vibration isolation performance even if optimal design parameters have variations due to manufacturing errors or material deterioration.